THE PROBLEM OF TYPOLOGY IN CHINESE ARCHAEOLOGY. (29th February 2016) - Hein, Anke
Abstract: Chinese and Western archaeologists (especially those of the anthropologically-oriented tradition) often seem to be talking past each other, not only because they are publishing in different languages, but also because of differences in theory and method. While most of the major theoretical works in Western languages are by now available in Chinese translations, hardly any English-language publications exist that explain Chinese approaches to archaeological method and theory. This article helps to bridge the gap by introducing the history of debates on archaeological method in China to a Western audience, focusing particularly on issues of typology and classification. Discussing in detail the merits—and issues—of approaches suggested by four of the most influential Chinese archaeologists (Li Chi, Xia Nai, Su Bingqi, and K. C. Chang), this article provides a deeper understanding of the preconditions of archaeological research in China. It also suggests future directions for archaeological work by local and foreign archaeologists, including but also going beyond the classification of the rich body of artifacts coming to light in Chinese excavations. 提要: 中國與西方的考古學家––特別是那些以研究人類學為目標的學者––在他們的論著中，經常出現各自表述的情況。除了使用不同的語言發表研究成果外，更根本的原因在於，中國與西方的考古學家有其各自獨特的理論框架與研究方法。時至今日，儘管大部份以西文書寫的重要理論已被譯為中文，然而，以中文書寫的理論與方法卻鮮少有英文譯本。本文的目的，是希望透過向西方的讀者介紹中國考古學研究方法的歷史，尤其是類型學與分類學的爭辯與發展，期待能在中西兩造學術傳統的鴻溝中，搭建溝通的橋樑。本文介紹李濟、夏鼐、蘇秉琦，與張光直等四位最具影響力的中國考古學家，藉由回顧他們的研究取徑與問題意識，深入檢視中國考古學的基本研究預設。在此基礎上，本文也將提供建言，指出中國及西方考古學家未來可能的工作方向。衷心期盼隨著愈來愈多重要考古遺存的發現，中國考古學能超越分類學的傳統，走出嶄新的道路。